1998
DOI: 10.1046/j.1468-2982.1998.1801023.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Allelic Distributions of the Serotonin Transporter Gene in Migraine Without Aura and Migraine with Aura

Abstract: Allelic variation of the human serotonin transporter gene (HSERT), a highly plausible candidate gene for susceptibility to migraine, was investigated in 266 individuals with migraine, including 173 having migraine without aura (MO), 94 having migraine with aura (MA), 18 with co-occurrence of MO and MA, plus 133 unaffected controls. The distribution of a polymorphism with different forms of a variable tandem number repeat (VNTR) in intron 2 were compared. The MO group had an over-representation of genotypes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 19 publications
3
79
1
1
Order By: Relevance
“…Molecular studies for genetic polymorphisms are being carried out for a number of different applications, such as anthropological and evolutionary studies [1, 2, 3, 4, 5, 6, 7, 8, 9], genetic disorders in different populations [10, 11, 12, 13, 14, 15, 16, 17], pharmacogenomics [18, 19, 20, 21], genetic identification of ethnic groups for forensic and legal applications [22, 23, 24], genetic identification of breed/stock in animals and plants for commercial applications [25]and conservation of germ plasm and applications to crop improvement [26, 27, 28, 29]. In designing these studies, an important issue to be considered is the minimum or optimum size of random sample required so that all the alleles/genotypes at one or more loci are observed with a certain prespecified probability [26, 27, 28, 31]and for reliably estimating allele frequency distributions by statistical methods [31].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies for genetic polymorphisms are being carried out for a number of different applications, such as anthropological and evolutionary studies [1, 2, 3, 4, 5, 6, 7, 8, 9], genetic disorders in different populations [10, 11, 12, 13, 14, 15, 16, 17], pharmacogenomics [18, 19, 20, 21], genetic identification of ethnic groups for forensic and legal applications [22, 23, 24], genetic identification of breed/stock in animals and plants for commercial applications [25]and conservation of germ plasm and applications to crop improvement [26, 27, 28, 29]. In designing these studies, an important issue to be considered is the minimum or optimum size of random sample required so that all the alleles/genotypes at one or more loci are observed with a certain prespecified probability [26, 27, 28, 31]and for reliably estimating allele frequency distributions by statistical methods [31].…”
Section: Introductionmentioning
confidence: 99%
“…Linkage studies of polymorphisms within the 5-HTT gene have indicated that a possible relationship exists between certain polymorphisms and susceptibility to depressive disorders (12,(16)(17)(18)(19)(20)(21)(22)(23)(24). Much interest has focused on a polymorphism within intron 2, which consists of a variable number of tandem repeats (VNTR) containing between 9 (Stin2.9), 10 (Stin2.10), and 12 (Stin2.12) copies of a 17-bp element (16)(17)(18)(19)(20). The difference in the number of copies of the repeated 17-bp element has been correlated with susceptibility to bipolar and unipolar disorder (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Much interest has focused on a polymorphism within intron 2, which consists of a variable number of tandem repeats (VNTR) containing between 9 (Stin2.9), 10 (Stin2.10), and 12 (Stin2.12) copies of a 17-bp element (16)(17)(18)(19)(20). The difference in the number of copies of the repeated 17-bp element has been correlated with susceptibility to bipolar and unipolar disorder (16)(17)(18)(19)(20). However, several other studies have produced data that seem to indicate that no link exists between 5-HTT intron 2 polymorphic regions and susceptibility to affective disorders (25,26).…”
mentioning
confidence: 99%
“…On the other hand, clinical and experimental data from several laboratories clearly indicate that the 5-HTT gene is one of the genetically contributing factors of migraine (Murphy et al, 2001). In migraine patients with and without aura it has been shown an altered allelic division of the 5-HTT (Ogilvie et al, 1998).…”
Section: Discussionmentioning
confidence: 99%